Death Sentences - Myre, Suzanne, 1961- (Book collections on Project MUSE., 2014)
Wry, witty, touching, and refreshing, with unpredictable plots and quirky characters who cope with death in their own curious ways, Death Sentences is the first translation of Mises à mort, the fifth short story collection from critically acclaimed French-Canadian author Suzanne Myre.